Seminal plasma cytokine levels in the diagnosis of chronic pelvic pain syndrome - Orhan, I; Onur, R; Ilhan, N; Ardiçoglu, A (Blackwell Science Asia, 2001)
Background: Chronic non-bacterial prostatitis/chronic pelvic pain syndrome (CPPS) are frequently encountered clinical entities characterized by painful and irritative voiding symptoms often referable to the prostate. Diagnosis usually depends on the symptoms and treatment mainly consists of reassurance, anti-inflammatory medications and antibiotics in the absence of a documented infection. To have objective diagnostic criteria, we determined the possible roles and diagnostic efficacies of soluble cytokines interleukin-1 beta (IL-1 beta), tumor necrosis factor-alpha (TNF-alpha), IL-2R, IL-6 and IL-8 in the seminal plasma of patients with different forms of CPPS. Methods: Seminal plasma was obtained from a total of 30 subjects who were evaluated in three groups. Each group comprised 10 patients having inflammatory CPPS, non-inflammatory CPPS and control subjects, respectively. The levels of IL-1 beta, IL-2R, TNF-alpha, IL-6 and IL-8 were measured in seminal plasma using chemiluminescence. Results: The level of IL-2R in all three groups was below measurable values. Interleukin-1 beta TNF-alpha IL-6 and IL-8 levels were elevated significantly in the two groups with CPPS compared with the control group (P < 0.05). Soluble cytokines showed a slight difference between patients with inflammatory CPPS and non-inflammatory CPPS, but this was not statistically significant (P > 0.05). Conclusion: Although there are individual variables between the discrimination of inflammatory and non-inflammatory CPPS, cytokines are frequently present and elevated in the expressed prostatic secretions from men with CPPS. Our results indicate that several soluble cytokines can be used to identify this chronic and long-term disease.
Keywords: chronic pelvic pain syndrome; cytokines; diagnosis